"Guttural Phrases" and "Vulgar Directives": The Evolution of Press Standards on Profanity. Issue 2 (2nd April 2020) - Pressman, Matthew
Abstract : Historically, major American newspapers have rarely printed expletives, obscenities, and vulgarities. When newspapers have deviated from that norm, it has usually been for one of four reasons: to report on a political figure cursing publicly; to convey realism in a story about a marginalized group (often a racial minority); to express the emotions of people in traumatic situations; or to quote faithfully from a book or film. Using digitized historical newspapers, industry publications, and archival sources, it is possible to analyze how the press's standards and practices on profanity have shifted from the 1960s to the Donald Trump era. The changes at the Associated Press and the New York Times are especially noteworthy, because their guidelines provide the model for many other news organizations.